From pain patient to junkie: An economic theory of painkiller consumption and its impact on wellbeing and longevity - Holger Strulik (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
In this paper, I propose a life cycle model of painkiller consumption that combines the theory of health deficit accumulation with the theory of addiction. Chronic pain is conceptualized as a persistent negative shock to lifetime utility that can be treated by pain relief medication. Individuals treated with opioid pain relievers (OPR) develop addiction, which increases their demand for opioids and reduces their welfare and life expectancy through side effects and potential overdose. I calibrate the model for a benchmark American and investigate the comparative dynamics of alternative drug characteristics, pain intensities, and ages of onsets of pain and their implications for welfare and life expectancy. Computational experiments are used to identify fully rational and imperfectly rational addiction behavior. Fully rational addicts quickly quit OPR use when new information about their addictive potential arrives. Imperfectly rational addicts further develop their addiction and switch to illicit opioid use. Likewise, a discontinued prescription helps fully rational addicts to quit quickly while it induces imperfectly rational individuals to take up heroin. I also discuss treatment of OPR addiction and the use of opioids in palliative care.
Keywords: D15; D91; I10; I12; 330; pain; pain relief; addiction; opioid epidemic; health deficits; life expectancy; illicit drugs